2018
DOI: 10.1073/pnas.1800525115
|View full text |Cite
|
Sign up to set email alerts
|

Rhinovirus induces an anabolic reprogramming in host cell metabolism essential for viral replication

Abstract: Rhinoviruses (RVs) are responsible for the majority of upper airway infections; despite their high prevalence and the resulting economic burden, effective treatment is lacking. We report here that RV induces metabolic alterations in host cells, which offer an efficient target for antiviral intervention. We show that RV-infected cells rapidly up-regulate glucose uptake in a PI3K-dependent manner. In parallel, infected cells enhance the expression of the PI3K-regulated glucose transporter GLUT1. In-depth metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
142
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(161 citation statements)
references
References 53 publications
6
142
0
Order By: Relevance
“…glycolysis) inhibition on SARS-CoV-2 replication. 2-deoxy-D-glucose (2-DG), an inhibitor of hexokinase, the rate limiting enzyme in glycolysis, had previously been shown to be effective against other viruses in cell culture and suppressed rhinovirus infection in mice 18 . Blocking glycolysis with non-toxic concentrations of 2-DG prevented SARS-CoV-2 replication in Caco-2 cells (2-DG, Fig.…”
Section: Pathways Changed By Sars-cov-2 Infectionmentioning
confidence: 99%
“…glycolysis) inhibition on SARS-CoV-2 replication. 2-deoxy-D-glucose (2-DG), an inhibitor of hexokinase, the rate limiting enzyme in glycolysis, had previously been shown to be effective against other viruses in cell culture and suppressed rhinovirus infection in mice 18 . Blocking glycolysis with non-toxic concentrations of 2-DG prevented SARS-CoV-2 replication in Caco-2 cells (2-DG, Fig.…”
Section: Pathways Changed By Sars-cov-2 Infectionmentioning
confidence: 99%
“…Therefore, it seems that HRSV, on the one hand, relies on the Warburg effect to promote the synthesis of the building blocks (nucleotides, amino acids, and lipids) for the virus structural components, and, on the other hand, on an anaplerotic reaction in which glutamine substitutes glucose as the predominant extracellular carbon source to feed the TCA cycle and generate energy. Rhinovirus infection also induces enhanced glucose uptake and increased levels of multiple nucleotides, indicating that this virus establishes an anabolic state in infected cells, in some aspects similar to HRSV [50]. Likewise, herpes simplex virus-1 (HSV-1) relies on glutamine uptake to feed the TCA cycle, while glucose is used to drive nucleotide synthesis [51].…”
Section: Plos Onementioning
confidence: 99%
“…Treatment with glycolysis inhibitor 2DG reverts the metabolism to lipogenesis. Thus GLUT inhibitors might open an alternative opportunity to address viral infection …”
Section: Possible Applications Beyond Oncologymentioning
confidence: 99%
“…Thus GLUT inhibitors might open an alternative opportunity to address viral infection. [54] Furthermore,t he transformation of progenitor cells to differentiatedc ells often involves as witch in the metabolic phenotype of the cell (Figure 3). Izumi et al recently demonstrated that the treatment of connective tissue with 2DG drives the differentiation to tendon cells and inhibits chondrogenesis, which is associated with poor tendon healing.…”
Section: Possible Applications Beyond Oncologymentioning
confidence: 99%